Analyzing the nonlinear p-Laplacian problem with the improved element-free Galerkin method. (March 2019) - Li, Xiaolin; Li, Shuling
Abstract: In this paper, the improved element-free Galerkin (IEFG) method is developed for the numerical analysis of the nonlinear p -Laplacian problem. In this method, the improved moving least squares approximation is adopted to form meshless shape functions, the Galerkin weak form is used to derive the nonlinear system of algebraic equations, and the subroutine 'fsolve' of MATLAB is adopted to deal with the strong nonlinearity. The computational formulas of the IEFG method for the p -Laplacian problem are obtained in detail. Numerical results show that the IEFG method for the p -Laplacian problem is convergent and has high computational accuracy.